Proceedings of the 18th International Seminar on Paste and Thickened Tailings 2015
DOI: 10.36487/acg_rep/1504_39_beveridge
|View full text |Cite
|
Sign up to set email alerts
|

Tailings co-disposal case study – art or science?

Abstract: Murray Zircon Pty Ltd operates the Mindarie Mineral Sands Project in South Australia comprising a mine and concentrator plant. The program for environmental protection and rehabilitation (PEPR) approved by the South Australia Department of Manufacturing, Innovation, Trade, Resources and Energy (DMITRE) requires diligent management of the tailings deposition and overall mine rehabilitation processes. The mining licence was granted based on a maximum permitted operational footprint of the open area of the mine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The results suggest that polymer treatment has the potential to significantly improve the overall performance of this type of mining operation, with particular benefit in the timely rehabilitation of mining land to agriculture. Furthermore, modelling suggests that the mining process could be optimised to the treatment by use of longer tailings cell sizes within the strip mining process; however, this aspect of the project is the subject of a parallel paper (Beveridge et al 2015).…”
Section: Summary For Mineral Sands Tailings Projectmentioning
confidence: 99%
“…The results suggest that polymer treatment has the potential to significantly improve the overall performance of this type of mining operation, with particular benefit in the timely rehabilitation of mining land to agriculture. Furthermore, modelling suggests that the mining process could be optimised to the treatment by use of longer tailings cell sizes within the strip mining process; however, this aspect of the project is the subject of a parallel paper (Beveridge et al 2015).…”
Section: Summary For Mineral Sands Tailings Projectmentioning
confidence: 99%
“…Owing to the increased application of forms of PT, studies to characterise the effects PT may have on post-deposition geotechnical behaviour of the treated slurry have been undertaken. Broadly, these studies have indicated the following effects of PT: lower consolidated densities at a given vertical effective stress and higher permeability at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Manzotti et al 2014;Beveridge et al 2015;Gholami & Simms 2015;Reid & Boshoff 2015;Riley et al 2015;Znidarcic et al 2015;Reid & Fourie 2016, 2018aAbdulnabi et al 2022), higher undrained shear strengths at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Beier et al 2013;Manzotti et al 2014;Cooling & Beveridge 2015;Gholami & Simms 2015;Reid & Fourie 2016Abdulnabi et al 2022) and higher CSL elevation (Reid & Fourie 2016), and various contrasting outcomes when examining the effects of PT on brittleness in undrained monotonic or post-cyclic shearing (Beier et al 2013;Gholami & Simms 2015;Reid & Fourie 2017) and drastically different penetrometer responses (Reid and Fourie 2018a), with a summary of recent studies provided by Reid and Fourie (2018b).…”
Section: Introductionmentioning
confidence: 99%